PENGARUH SOSIALISASI TERHADAP PENINGKATAN PENGETAHUAN MASYARAKAT DESA LAMBROE BILEU ACEH BESAR - Lensoni; Andriaty, Syarifah Nora; Zahara, Hafni; Kala, Pasyamei Rumbune; Anggriani, Yayu; Raisah, Putri; Karma, Taufik; Khumairah, Rosika; Sari, Muliya; Naira, Alifya Zuriva (Transpublika Publisher, 2022)
Stunting that has occurred if not balanced with catch-up growth (chasing growth) results in decreased growth, stunting problems are public health problems related to increased pain risk, death and inhibitions to growth both motor and mental. This study used a pre-expriemental design type of one group pretest-posttest design. The population in this study was the people of Lambroe Bileu Village. The sampling technique used is total sampling. In the independent variable research, it is the provision of counseling on stunting, while the dependent variable is the knowledge of the people of Lambroe Bileu Aceh Besar Village. Based on the results of the study, where after counseling, mothers' knowledge about stunting increased from before being given counseling. Where the percentage before counseling is 37.5% to 87.5% after counseling. If there is an increase in respondents after counseling, it can be said that providing education with the counseling method is very effective for maternal knowledge about stunting so as to reduce the risk of stunting cases in the community.